KORELASI KEBIASAAN MEMBACA MANGA DENGAN KEMAMPUAN KANJI PADA MAHASISWA BAHASA JEPANG UNIVERSITAS NEGERI PADANG - Annisa Rahmawati; Maulluddul Haq (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2022)
This study aims to see how strong the relationship between reading manga habits and students' kanji abilities is. The design of this study is a correlation design. The population in this study amounted to 100 students. The sampling technique used in this study was purposive sampling with a sample of 80 students. This study uses a questionnaire to see the habit of reading manga and a test to determine the students' kanji ability. The results of this study are: First, the average value of students' habits in reading manga is 77.33. Second, the students' kanji ability is 82.25. Third, the correlation coefficient of the two variables; manga reading habit and kanji ability is 0.784. Thus, the researcher proves that  is rejected and  is accepted, meaning that there is a significant relationship between students' habits in reading manga and students' kanji abilities.